Correction: Efficacy and safety of guselkumab and adalimumab for pustulotic arthro-osteitis and their impact on peripheral blood immunophenotypes (Arthritis Research & Therapy, (2022), 24, 1, (240), 10.1186/s13075-022-02934-3) - Ueno, Masanobu; Miyagawa, Ippei; Miyazaki, Yusuke; Hanami, Kentaro; Fukuyo, Shunsuke; Kubo, Satoshi; Nakayamada, Shingo; Tanaka, Yoshiya (Arthritis Research & Therapy, 2023)
Following publication of the original article [1], the authors reported an error in Additional file 1: Figure S1, Panel (C), subpanel c) a description regarding the gating strategy for the activated Th17 cells. The data currently reads.
CRIS-Team Scopus Importer:2023-03-03